Doing Well by Doing Good- CSR in a Global Context - Magdalena Popowska; Beata Ratkowska (Institute of Economic Research (IER), 2017)
Nowadays, there is a general understanding that stakeholders are crucial for the successful enterprise. There is also a need to think about Corporate Social Responsibility (CSR) in a global context. Never before corporations enjoyed so much power and authority. Corporations need to evolve, re-think their strategies and change their processes accordingly. However, as of now, there is no agreed way of measuring overall sustainability of actions of each company. There is a great need for holistic studies of CSR, analyzing in details the value created, from stakeholders point of view. This paper is an attempt to propose a way of looking at corporate social responsibility in line with current methodologies and frameworks focusing on value creation. Currently there is no one definition of global CSR to be used, nor there is one comprehensive methodology to describe it. Instead there is abundance of theories and frameworks. This paper proposes one definition and presents a method of analysis of the global corporate commitment to CSR approach. The main concern of this paper is to offer an insight into different ways companies can create value for various stakeholders groups. To narrow the scope of the conducted analysis, the authors identified 13 companies, potential sustainability winners, from products industry Analyzed were both, CSR execution capacity and CSR value creation assessed on basis of compliance with identified CSR basic actions catalogue. Conducted analysis indicated that products companies are aware of needs and expectations of various stakeholders and are good at meeting them. Although assessed companies managed to link sustainability with their strategies, they did not achieve transforming sustainability into core of their business.
Keywords: Q01; 330; CSR; sustainability; CSR reporting; CSR measuring; global CSR